Biological evaluation of selected metronidazole derivatives as anti-nitroreductase via in silico approach - Adeoye, Moriam Dasola; Oyebamiji, Abel Kolawole; Ashiru, Mojeed Ayoola; Adigun, Rasheed Adewale; Olalere, Olabisi Hadijat; Semire, Banjo (Eclética Química, 2022)
The 1-(2-hydroxyethyl)-2-methyl-5-nitroimidazole (2HMN) is a powerful antibacterial and antiparasitic drug used alongside other drugs against Helicobacter pylori infection and was investigated the effects of substituents: –OH (A), H (B), –SPh (C), –COOH (D), –NO2 (E) and –OCH3 (F) on the interactions of 2HMN with the target nitroreductase Rdxa protein for the treatment of the infection. Spartan 14 (optimization), PyMOL 1.7.4.4 (to treat downloaded protein), Autodock Tool (locate protein binding site), Autodock vina 1.1.2 (docking calculation) were used to discover the nonbonding interaction between docked complexes using SWISSADME and Pre-ADMET software. The band gaps order for the studied compounds were C < A < F < B < D < E, a probability of highest charge distribution and activity for SPh substituted derivatives and the ligands conformed to the Lipinski’s rule of five. Compounds D and E are noninhibitors and nonsubstrate for cytochrome P450 2C9, P450 2D6, P450 2C19 with the same efficient calculated binding affinity (–21.3 kJ mol–1) and inhibition constant (7.8) comparable to the standard compound A.